[FE1091] Regulations Governing the Usage of Reclaimed Water as an Alternative Water Source for Agricultural Irrigation in Florida - Leticia Braune; Gulcan Onel; Tatiana Borisova; Pilar Useche (EDIS, 2021)
Fresh water is becoming increasing scarce as the world population grows rapidly. Reclaimed water from alternative sources can be used to help offset the demand for fresh surface water and groundwater in agriculture. To ensure that pathogenic or trace chemical constituents in reclaimed water do not pose a threat to human health and the environment, state and federal governments impose regulations governing reclaimed water use. This fact sheet documents the rules and regulations governing the use of reclaimed water from alternative water sources in Florida agriculture. Target audiences include growers exploring alternative water use for agriculture, non-core professionals, core professionals, and the public.